Pengaruh Tipografi pada Era Massimo Vignelli terhadap Tipografi Michael Bierut - Irwan Harnoko; Dria Setiautami (Bina Nusantara University, 2011)
Massimo Vignelli is a senior graphic designer lived in New York, as a vocal modernism against post-modernism. His statement firmly opposing post-modernism in several occasions: interview in Helvetica the movie, typeradio, talkshow, and some articles in Looking Closer or AIGA Journal. Graphic design works of Massimo Vignelli reflected his characteristic, which is firmly choosing typeface. Typefaces of Vignelly are around 5 typefaces: Bodoni, Helvetica, Times Roman, Century, and Futura. The article uses formal analysis method. The writers collected materials about Michael Bierut, Massimo VIgnelli and Tibor Kalman from books and websites. The writers compare the typeface opinion of Massimo Vignelli (modernism designer), Michael Bierut designer (transition era designer from modernism to post-modernism), and Tibor Kalman (a designer in A Century of Graphic Design, as the influencer of Bierut’s betrayal over Vignelli).